Study of phenolic characterization of walnut wood extracts for potential use in oenology - Miglior, Nicolò (2022)
Mestrado em Engenharia de Viticultura e Enologia (Double degree) / Instituto Superior de Agronomia. Universidade de Lisboa / Faculdade de Ciências. Universidade do Porto